2021
DOI: 10.1021/acs.accounts.0c00826
|View full text |Cite
|
Sign up to set email alerts
|

Dreams, False Starts, Dead Ends, and Redemption: A Chronicle of the Evolution of a Chemoinformatic Workflow for the Optimization of Enantioselective Catalysts

Abstract: Conspectus Catalyst design in enantioselective catalysis has historically been driven by empiricism. In this endeavor, experimentalists attempt to qualitatively identify trends in structure that lead to a desired catalyst function. In this body of work, we lay the groundwork for an improved, alternative workflow that uses quantitative methods to inform decision making at every step of the process. At the outset, we define a library of synthetically accessible permutations of a catalyst scaffold with the philos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 66 publications
0
48
0
Order By: Relevance
“…The relevance of chemically meaningful features was shown by attempting extrapolative predictions using randomized labels, which led to worsened performance. 155 Huang et al 156 focused on improving the featurization of the Spectral London Axilrod-Teller-Muto (SLATM) structure-based representation in order to develop and improve the performance of kernel ridge regression models for the enantioselectivity prediction. They introduced reaction-based representations and exploited metric learning and supervised feature selection techniques to filter the information contained in the molecular representations.…”
Section: Selectivitymentioning
confidence: 99%
“…The relevance of chemically meaningful features was shown by attempting extrapolative predictions using randomized labels, which led to worsened performance. 155 Huang et al 156 focused on improving the featurization of the Spectral London Axilrod-Teller-Muto (SLATM) structure-based representation in order to develop and improve the performance of kernel ridge regression models for the enantioselectivity prediction. They introduced reaction-based representations and exploited metric learning and supervised feature selection techniques to filter the information contained in the molecular representations.…”
Section: Selectivitymentioning
confidence: 99%
“…6 Alternatively, 3D descriptors represent general strucutural information, and thus models on 3D structures may identify correlations without requiring knowledge of the detailed reaction mechanism. 10 These methods have already been applied in asymmetric catalysis, using calculated 3D structures with grid-based binary feature vectors, such as Comparative Molecular Field Analysis (CoMFA). [11][12][13][14][15] The Denmark group reported a modification of grid-based methods with non-binary features based on distribution of conformations to account for their flexibility, and demonstrated that the model can predict higher selectivity even in the absence of such examples in the training dataset.…”
Section: Main Textmentioning
confidence: 99%
“…1,2 However, the complex nature of modern reactions, and the subtle variation in reaction conditions between similar substrates, can make the selection challenging. 3,4 Predictive models like multivariate linear regression (MLR) have been advanced to address this issue [5][6][7][8][9][10] with numerous successful applications in selective catalyst 11,12 and reaction 13 development having been recorded. However, such statistical models need to be both reliable and interpretable to be widely accepted by practitioners.…”
Section: Introductionmentioning
confidence: 99%